Mitigation of the pressure fluctuation arising from high-speed train intersection in tunnels using enlarged tunnel ends. (October 2022) - Lu, Yibin; Wang, Tiantian; Yang, Mingzhi; Zhang, Lei; Shi, Fangcheng; Zhu, Yu; Tian, Xudong
Highlights: Study the mitigation effect of pressure fluctuations caused by train intersection in a tunnel with the enlarged end. Consider the effects of the total length of tunnels and unit number of trains on the optimal length of the enlarged section. Analyse the mitigation principle of the pressure fluctuations impacted upon trains. Obtain an optimal length coefficient to attain the maximum mitigation of the pressure fluctuations. Abstract: Intense pressure fluctuations generated by the intersection of high-speed trains (HSTs) in a tunnel are unfavourable for the comfort of passengers and the safety of HSTs and tunnel facilities. This study numerically investigated the mitigation principle of the pressure fluctuation impacted upon HSTs using the enlarged tunnel end with taking into account the total tunnel length and the unit number of HSTs. Moving model tests were also performed to validate the numerical method based on the unsteady RANS equations and RNG k - ε turbulence model. The numerical results show that the enlarged end of a tunnel can manifestly alleviate the negative pressure induced by the train intersection and the length ratio of the optimal length of the enlarged section to the total length is in the range of 0.26–0.28. The optimal length of the enlarged section can be implemented by synchronising the contact of the derived waves with the train intersection. Moreover, the increase in the marshalling number of HST augments the mitigation effect of the enlarged section. This study gives insight into the mitigation of the pressure fluctuation in tunnels and can provide valuable data and a theoretical basis for the tunnel design when considering the aerodynamic effect of HST intersection.